2014
DOI: 10.1007/s00439-014-1476-7
|View full text |Cite|
|
Sign up to set email alerts
|

Missing heritability of common diseases and treatments outside the protein-coding exome

Abstract: Genetic factors strongly influence risk of common human diseases and treatment outcomes but the causative variants remain largely unknown; this gap has been called the ‘missing heritability’. We propose several hypotheses that in combination have the potential to narrow the gap. First, given a multi-stage path from wellness to disease, we propose that common variants under positive evolutionary selection represent normal variation and gate the transition between wellness and an ‘off-well’ state, revealing adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 120 publications
(149 reference statements)
1
43
0
Order By: Relevance
“…At that, HLA-DRB1*15:01 alone explains about 20 % of heritability (Lill 2014). There are several explanations of this "missing heritability" (Manolio et al 2009;Sadee et al 2014) in complex diseases, of which MS is a typical example.…”
Section: Main Conclusion and Future Perspectivesmentioning
confidence: 96%
See 2 more Smart Citations
“…At that, HLA-DRB1*15:01 alone explains about 20 % of heritability (Lill 2014). There are several explanations of this "missing heritability" (Manolio et al 2009;Sadee et al 2014) in complex diseases, of which MS is a typical example.…”
Section: Main Conclusion and Future Perspectivesmentioning
confidence: 96%
“…However, we apparently are at the initial stage of this process. Recent estimations based on sibling studies (Sadee et al 2014) suggest that the MS risk loci identified to date explain only about 27 % of its total heritability (Lill 2014). At that, HLA-DRB1*15:01 alone explains about 20 % of heritability (Lill 2014).…”
Section: Main Conclusion and Future Perspectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…186 One source of this “missing heritability” (discrepancy between the predicted and observed genetic risk) could be rare or structural variants that contribute to disease risk but were not covered in early GWAS (newer GWAS platforms have a greater representation of these variants). Another reason for missing heritability could be gene-gene and gene-environment interactions.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 99%
“…Current genome-wide association studies (GWAS) reveal a large gap between known causal genes and the observed heritability of common diseases and treatment outcomes (Sadee et al, 2014). Another limitation of GWAS is that each locus nominates a large group of SNPs in linkage disequilibrium, such that causal and neutral variants cannot easily be distinguished.…”
Section: Introductionmentioning
confidence: 99%